Evaluation of OCT2‐mediated drug-drug interactions between ulotaront and metformin in subjects with schizophrenia - Guangqing Xiao; Hironobu Tsukada; Yu‐Luan Chen; Lei Shi; Seth C. Hopkins; Gerald R. Galluppi (Wiley, 2024)
Abstract Ulotaront (SEP‐363856) is a TAAR1 agonist, with 5‐HT1A agonist activity, currently in clinical development for the treatment of schizophrenia. In vitro studies indicate ulotaront is an OCT2‐specific inhibitor with IC50 of 1.27 μM. The primary objective of this study is to determine if a single dose of ulotaront affects the PK of metformin, an index substrate of OCT2, in subjects with schizophrenia. In a randomized, single‐blind, 2‐period crossover study, 25 adults with schizophrenia received a single dose of metformin‐HCl 850 mg (approximately 663 mg metformin) with and without coadministration of 100 mg ulotaront. The plasma samples were analyzed by fully validated LC-MS/MS methods. The primary PK endpoints for metformin were AUCinf, AUClast, Cmax, and tmax. The highest‐anticipated clinical dose of ulotaront (100 mg) had no statistically significant effect on the PK of a single dose of metformin based on Cmax and AUCinf. Geometric least squares mean ratios were 89.98% and 110.63%, respectively, with the 90% confidential interval (CI) for each parameter contained within 80%-125%. Median tmax was comparable across the treatments. Ulotaront does not act as a perpetrator of OCT2‐mediated DDI against metformin. Co‐administration of ulotaront is not expected to require dose adjustment of metformin or other drugs cleared by OCT2.